Impact of climate change on plant species richness across drylands in China: From past to present and into the future. (December 2021) - Sun, Ying; Sun, Yuan; Yao, Shuran; Akram, Muhammad Adnan; Hu, Weigang; Dong, Longwei; Li, Hailing; Wei, Maohong; Gong, Haiyang; Xie, Shubin; Aqeel, Muhammad; Ran, Jinzhi; et al.
Highlights: Random forest models were employed to estimate plant species richness in drylands. Plant richness increased from last interglacial and is projected to increase. Different plant lifeforms exhibit varying sensitivities to climate change. Herbaceous species respond more rapidly to climate change than woody species. Abstract: It is commonly believed that climate plays an important role in shaping the patterns of plant species richness. However, it remains unclear how climate may affect plant richness across large spatial scales and also over long-terms, for example across massive arid regions during the Quaternary and into the future. To fill this knowledge gap, we examined the long-term trends in plant species richness across vast drylands in China based on our newly developed climate-species richness models. We first generated optimal random forest models based on the relationships between the current (CUR, 1970–2000) annual, perennial, woody and total species richness and climatic variables. We subsequently hindcasted and forecasted plant species richness in five other periods: last interglacial (LIG, 120, 000–140, 000 years BP), last glacial maximum (LGM, about 22, 000 years BP), mid-Holocene (MH, about 6000 years BP), 2041–2060 (2050), and 2061–2080 (2070). Our results showed that total and herbaceous species richness exhibited similar patterns that were driven by temperature and precipitation. Both groups of species formed a transition zone between arid and semi-arid regions in all periods except LIG. In contrast, woody species richness did not form any transition zone because it was regulated mainly by temperature. Furthermore, the mean richness of herbaceous, woody and all species exhibited gradually increasing trends from LIG to 2070 across drylands in China. On the one hand, herbaceous species were much more sensitive to climate change than woody species. On the other hand, plant species richness in mountain-basin systems and Taklamakan Desert regions were more sensitive to climate change than in meadows and steppes. These results shed new insights into the past and future changes in plant species richness over vast drylands and provide valuable information for future conservation efforts under global warming.